Effect of Atmospheric Non-Thermal Plasma on Adhesion Process of Pseudomonas Spp Bacteria - Khalaf, Thamir H; Hussein, Mohammed Ubaid; Al-Fahdawi, Abdul Rahman M G (Al-Nahrain Journal of Science, 2018)
Non-thermal atmospheric pressure plasma has emerged as a new promising tool in medicine. The effectiveness of an Atmospheric Non Thermal Plasma (ANTP) for clinical and biological applications are studied. The effort achieved in this work includes a designing of plasma generating system and examine it on some medical and biological parameters. The dependencies of decreasing the adhesion of bacteria on the applied voltage and distance have been recorded. A series of experiments reveal that this effectiveness is due to the ability of direct discharge to bring charges to samples due to generation of so many mediators like reactive nitrogen species and free radicals. Increasing applied voltage and decreasing gap distance effect on decreasing Numbers of bacteria attached to epithelial cells to half.